Development of Telegram-Based Home Automation and Data Acquisition System - Widodo Budiharto; Heri Ngarianto (Bina Nusantara University, 2024)
Home automation and data acquisition system using Telegram application makes us able to automate tasks related to control and monitoring through a system installed at home or building. In this research, we propose an algorithm and architecture used for Telegram-based home automation and data acquisition with environmental sensors such has temperature, humidity, CO2, and Volatile Organic Compounds (VOC) measurement (air quality) as indicator of good air quality. Based on experiment, we can detect the condition of environment, control the relay and the system able to give information about the quality of air from smartphone.